1994
DOI: 10.1095/biolreprod50.3.702
|View full text |Cite
|
Sign up to set email alerts
|

Type VI Collagen in the Rat Testis: Monoclonal Antibody, Isolation, and Localization during Development1

Abstract: To investigate the components of the seminiferous tubule extracellular matrix (ST-ECM), monoclonal antibodies were raised against ST-ECM. One of these (15B6) recognized the nonreduced form of type VI collagen. With this antibody as a probe, type VI collagen was isolated from an SDS-urea extract of ST-ECM. It took a tetrameric form, and upon reduction dissociated into a major 140-kDa band and two bands at 190 and 210 kDa. Developmental changes in the distribution of type VI collagen were investigated by immunof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…These changes demonstrate that the seminiferous tubule BM is undergoing subtle changes in its composition during the postnatal period before the onset of germ cell meiotic divisions. Previous studies have shown a change in the distribution of collagen VI within the postnatal rat testis, from an exclusive interstitial localization in the fetal and neonatal testis to a close association with the seminiferous tubule BM by Day 14 [18]. Our observations confirm these studies and demonstrate that the association of collagen VI with BMs occurs progressively from Day 10 to Day 20.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These changes demonstrate that the seminiferous tubule BM is undergoing subtle changes in its composition during the postnatal period before the onset of germ cell meiotic divisions. Previous studies have shown a change in the distribution of collagen VI within the postnatal rat testis, from an exclusive interstitial localization in the fetal and neonatal testis to a close association with the seminiferous tubule BM by Day 14 [18]. Our observations confirm these studies and demonstrate that the association of collagen VI with BMs occurs progressively from Day 10 to Day 20.…”
Section: Discussionsupporting
confidence: 90%
“…Collagen VI is initially restricted to the interstitial matrix between seminiferous cords of the fetal and early postnatal rat testis, and subsequently it is observed to be associated with the BM around Sertoli cells and peritubular cells by Day 14, when these cell types are beginning to differentiate [18]. In the mouse, the appearance of the ao3(IV) isoform chain of collagen IV in the BMs around seminiferous tubules coincides with the period when spermatogonia begin to proliferate and then migrate to the BM, suggesting that collagen ao3(IV) chains may have a role in these processes [19].…”
Section: Introductionmentioning
confidence: 99%
“…In the normal developing rat testis, type VI collagen has been reported to fill the interstitial spaces between fetal cords, but in the adult, the same type of collagen was shown confined to the LIMM of the tubules and of the adventitia of the vessels [33,34]. Furthermore, it was concluded that type VI collagen was distributed independently from type I collagen fibrils in the interstitial spaces and that it was excluded from the basal lamina of the Sertoli cells [34], suggesting that peritubular myoid cells may be, at least in part, responsible for the deposit of type VI collagen.…”
Section: Limm Of the Seminiferous Tubulementioning
confidence: 99%
“…The ST-ECM was homogenized and used for immunization (Sawada and Yazama, 1994). Hybridomas were produced by fusing splenocytes from immunized BALB/c mice with X63-Ag8-6.5.3 myelomas with polyethylene glycol 1530 (Sigma Chemical Co.), according to the standard procedure (Galfre and Milstein, 1981).…”
Section: Antibodiesmentioning
confidence: 99%